Factors associated with the improvement of professional performance through continuing medical education - Rolando Bonal Ruiz; Alejandro Antuan Díaz Díaz; Reina Sotomayor Escalona (Universidad de Ciencias Médicas de La Habana, 2020)
Introduction: Despite the efforts to improve the quality of self-improvement activities, the effective factors that guarantee improvement in professional performance produced by these activities are unknown. Objective: To identify the factors associated with the improvement of professional performance through continuing medical education. Material and Methods:Aqualitative descriptive study was carried out. It consisted on a review and documentary analysis, especially systematic reviews of publications in journals indexed in SciELO, Medline, and Lilacs databases. Development: Eleven factors that could facilitate the effectiveness of improvement activitieswere identified.However, it is considered a non-exhaustive list that could be corrected. It is suggested that there are external and internal factors that can influence professional performance. Conclusions: Once the effective factors that contribute to the improvement of professional performancethrough activities have been identified, it is necessary to take these elements into account when planning future training plans for health professionals.